On the Edge: Sacred Boundary Making in the Time of Covid-19 - Knott, Kim (Political theology, 2025)
Working with the concept of "the edge," and its relationship to boundaries, spaces and distinctions, I consider what inviolable beliefs and values surfaced during the first phase of Coronavirus. As people were exposed to new risks and dangers, sent into isolation by their governments and forced online, how was the sacred impacted, and what places and boundaries became significant? I draw on theories from urban design, cognitive linguistics and anthropology to situate the "sacred" as a category boundary before undertaking an interpretive exploration of three cases: the domestic secular sacred, alternative spirituality and evangelical Christian practice. These illustrate the production of the sacred in a period of crisis, with new boundaries acquiring significance, and established but also novel rituals employed to reify non-negotiable beliefs. But two verities hold true. People remained concerned to protect those things they deemed sacred, and they sought the solace of community and solidarity with others.